1997
DOI: 10.1046/j.1365-2249.1997.3431244.x
|View full text |Cite
|
Sign up to set email alerts
|

Human T cell responses to recombinant mite antigens of Dermatophagoides farinae

Abstract: SUMMARYWe studied T cell responses to four glutathione S transferase (GST)-fused mite antigens prepared in our laboratory using peripheral blood lymphocytes from mite-sensitive patients with bronchial asthma. Of the four recombinant antigens, purified GST-Mag3 had the strongest ability to cause patients' lymphocytes to proliferate, and its potency was almost comparable to that of crude mite bodies (Dfb) and faeces (Dff) antigens and a purified major antigen, Der f 2. The responder lymphocytes were mainly T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…It is likely the size and the frequency of the responses have been underestimated because the apolipophorin properties of the allergen make it difficult to examine. The T cell stimulation information presented here and by Fujii et al [6]show the allergens are more stimulatory than the major group 2 allergens. The relative difference in the ability of the Mag 1 and Mag 3 fragments to be produced in E. coli and to stimulate T cells in the studies reported for D. pteronyssinus and D. farinae may be genuine differences between the species or could represent different stabilities of the fragments.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It is likely the size and the frequency of the responses have been underestimated because the apolipophorin properties of the allergen make it difficult to examine. The T cell stimulation information presented here and by Fujii et al [6]show the allergens are more stimulatory than the major group 2 allergens. The relative difference in the ability of the Mag 1 and Mag 3 fragments to be produced in E. coli and to stimulate T cells in the studies reported for D. pteronyssinus and D. farinae may be genuine differences between the species or could represent different stabilities of the fragments.…”
Section: Discussionsupporting
confidence: 51%
“…The ability of the recombinant polypeptide fragments Mag 1 and Mag 3 to stimulate the proliferation of T cells from peripheral blood mononuclear cells was examined by Fujii et al [6]. Their initial test showed that only Mag 3 appeared stimulatory so this was examined further.…”
Section: T-cell Responses To Group 14 Allergensmentioning
confidence: 99%
“…The ability of recombinant Der f 2, Der f 10 and Mag 1, 3 (fragments of Der f 14) to stimulate T-cell proliferation was compared [74]. The responses to the high IgE-binding allergens Der f 2 and Mag 3 peptide were high and the responses to Mag 1 and Der f 10 were low.…”
Section: T-cell Responses To Purified Allergensmentioning
confidence: 99%
“…The peptide, Mag 3, which was an arbitrary fragment expressed from a partial cDNA clone from D. farinae, was shown to be a part of a 177,000 MW allergen with the same strength of reactivity as Der f 1 and 2 in both IgE-binding and T-cell assays [49, 74]. The high-molecular-weight protein did not contain lipid or carbohydrate moieties and the staining of histological section showed it was distributed throughout the body [49].…”
Section: Group 14 Allergensmentioning
confidence: 99%
“…This frequency and magnitude of binding was similar to the major allergen Der f 2. Moreover, T–cell–proliferative responses to Mag 3 were large and correlated with responses to Der f 2 [25]. …”
Section: Discussionmentioning
confidence: 99%